Kryminał - okna i świat = The crime novel - windows and the world - Ruszczyńska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an outline within which the author attempts to find the answer to some key issues associated with changes in modern Polish crime novels of the last decade. The main problem revolves around the determinants of the crime novel as a hybrid form which abandons the traditional poetics in favour of an open formula and relationships with the social novel. The author also addresses the crime novel`s polyphonic and cyclical nature, both in its epic and interactive (dialogue with the reader) contexts.
Keywords: powieść kryminalna; literaturoznawstwo; proza polska - 21 w.